2013
DOI: 10.1053/j.gastro.2013.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Use of Laser Capture Microdissection to Map Hepatitis C Virus–Positive Hepatocytes in Human Liver

Abstract: BACKGROUND & AIMS Hepatitis C virus (HCV) predominantly infects hepatocytes, but many hepatocytes are not infected; studies have shown that HCV antigens cluster within the liver. We investigated spatial distribution and determinants of HCV replication in human liver samples. METHODS We analyzed liver samples from 4 patients with chronic HCV infection (genotype 1, Metavir scores 0–1) to estimate the proportion of infected hepatocytes and the amount of HCV viral RNA (vRNA) per cell. Single-cell laser capture m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
113
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 76 publications
(129 citation statements)
references
References 23 publications
16
113
0
Order By: Relevance
“…2B). Laser capture microdissection was used to enrich hepatocytes from liver tissue collected from subjects ISV-1 and ISV-2, as previously described (24): RNA was extracted and studied by NGMS. HHpgV-1 reads were identified in the hepatocytes of subject ISV-1 but not from subject ISV-2.…”
Section: Resultsmentioning
confidence: 99%
“…2B). Laser capture microdissection was used to enrich hepatocytes from liver tissue collected from subjects ISV-1 and ISV-2, as previously described (24): RNA was extracted and studied by NGMS. HHpgV-1 reads were identified in the hepatocytes of subject ISV-1 but not from subject ISV-2.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies performed by in situ PCR (33,34), fluorescence microscopy (35), or laser-capture microdissection followed by RT-PCR (36,37) indicated that the distribution of HCV RNA in the liver is focal and that the percentage of infected hepatocytes is low (never >35% of the total population). However, the focal distribution of HCV-infected cells (37) cannot explain the restricted viral replication that we detected exclusively within the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…While we cannot absolutely exclude such a possibility, it seems unlikely for several reasons. First, multiple modalities, including two-photon fluorescence microscopy (2), fluorescent in situ RNA hybridization (31), and single-cell laser capture microdissection coupled with qRT-PCR (32), all indicate that HCV replicates very inefficiently with limited expression of viral proteins and RNA within individual hepatocytes in the infected human liver. Infected hepatocytes are estimated to contain no more than 100 copies of the HCV genome (33), far fewer than JFH1 (or even H77S.3) virus-infected Huh-7.5 cells.…”
Section: Discussionmentioning
confidence: 99%